Contrasting Temperature Sensitivity of CO2 Exchange in Peatlands of the Hudson Bay Lowlands, Canada. Issue 7 (18th July 2019) - Helbig, M.; Humphreys, E. R.; Todd, A.
Abstract: It remains uncertain how the net ecosystem CO2 exchange (NEE) of diverse peatlands will respond to warming. Here we compare five years of eddy covariance measurements of NEE and estimates of gross primary productivity and ecosystem respiration between a fen dominated by deciduous vegetation and an adjacent bog with evergreen vegetation in the Canadian Hudson Bay Lowlands. At the bog, daily net CO2 uptake lasted from snowmelt to snow cover onset, while at the fen, net CO2 uptake was delayed in spring and ended earlier in fall. Greater midsummer net CO2 uptake at the fen compensated for shoulder season net CO2 losses resulting in similar annual NEE at the two sites (fen: −52 ± 16 g C m −2, bog: −80 ± 14 g C m −2 ). Observations of a satellite‐based productivity index also suggest lower shoulder season and higher peak vegetation productivity at these deciduous versus evergreen plant‐dominated peatlands. The response of NEE to warmer weather differed between sites. Warming during the shoulder seasons increased net CO2 uptake at the evergreen plant‐dominated bog, while it increased net CO2 losses at the fen where deciduous leaves had not yet emerged or had senesced. In contrast, warmer weather during the peak growing season appeared to reduce net CO2 uptake more at the bog than the fen resulting from both increasing ecosystem respiration and decreasing gross primary productivity. In the short term, warming will likely decrease annual net CO2 uptake of these and similar peatlands, although the magnitude will depend on factors including vegetation dynamics and seasonality of warming. Plain Language Summary: Peatland ecosystems are large reservoirs of carbon as their long‐term productivity slightly exceeds decomposition. Peatlands are also highly diverse ecosystems with some dominated by evergreen vegetation, while others are dominated by deciduous vegetation, which shed leaves in the fall and grow new leaves in spring. Due to these different leaf strategies, we expect that the net exchange of carbon dioxide (CO2 ) between peatlands and the atmosphere will differ through the year and respond differently to warmer weather. Five years of measurements of CO2 exchange between land and atmosphere at two adjacent peatlands with contrasting vegetation revealed contrasting seasonal patterns in productivity (CO2 uptake) and respiration (CO2 loss to the atmosphere) but similar annual CO2 uptake. During the summer, net CO2 uptake decreased with warmer air temperatures at both sites. In spring, the evergreen plant‐dominated vegetation benefitted more from warmer air temperatures as plants started growing immediately following snowmelt while leaves of deciduous plants had not yet emerged. These contrasting productivity patterns were also reflected in satellite‐based observations throughout the study region of the Canadian Hudson Bay Lowlands. Our study suggests that currently, warmer air temperatures likely reduce the amount of CO2 taken up by these peatlands. Key Points: Annual CO2 sink strength of two peatland ecosystems are similar despite different evergreen and deciduous vegetation communities Warmer peak growing season temperature largely decreases net CO2 uptake of both evergreen and deciduous plant‐dominated peatlands Warmer shoulder season temperature decreases net CO2 uptake at the deciduous‐dominated peatland